Reward-related gustatory and psychometric predictors of weight loss following bariatric surgery: a multicenter cohort study. Issue 3 (9th February 2021) - Ribeiro, Gabriela; Camacho, Marta; Fernandes, Ana B; Cotovio, Gonçalo; Torres, Sandra; Oliveira-Maia, Albino J
ABSTRACT: Background: Reward sensitivity has been proposed as a potential mediator of outcomes for bariatric surgery. Objectives: We aimed to determine whether gustatory and psychometric measures of reward-related feeding are predictors of bariatric-induced weight loss. Methods: A multicenter longitudinal cohort study was conducted in patients scheduled for bariatric surgery (surgical group), assessed at baseline and 2 follow-up assessments. Predictions of % weight loss from baseline (%WL) according to baseline gustatory measures, including intensity and pleasantness ratings of sweet and other tastants, and psychometric measures of reward-related feeding behavior, including hedonic hunger scores, were assessed with multivariable linear regression. Exploratory analyses were conducted to test for associations between %WL and changes in gustatory and psychophysical measures, as well as for comparisons with data from patients on the surgery waiting list (control group). Results: We included 212 patients, of whom 96 in the surgical group and 50 in the control group were prospectively assessed. The groups were similar at baseline and, as expected, bariatric surgery resulted in higher %WL (BTreatment-Time   = 2.4; 95% CI: 2.1–2.8; P   < 0.0001). While variation in gustatory measures did not differ between groups, in the surgery group baseline sweet intensity predicted %WL at the primary endpoint (11 to 18 months postoperatively; β = 0.2; B = 0.2, 95% CI: 0.02 to 0.3; P   = 0.02), as did hedonic hunger scores (β = −0.2; B = −2.0, 95% CI: −3.8 to −0.3; P   = 0.02). Furthermore, at this endpoint, postsurgical reduction of sweet taste intensity and acceptance of sweet foods were associated with %WL (β = −0.3; B = −3.5, 95% CI: −5.8 to −1.3; P   = 0.003, and β = −0.2; B = −4.7, 95% CI: −8.5 to −0.8; P   = 0.02, respectively). The use of sweet intensity as a predictor of weight change was confirmed in another bariatric cohort. Conclusions: Sweet intensity ratings and hedonic hunger scores predict %WL after surgery. The variability of sweet intensity ratings is also associated with %WL, further suggesting they may reflect physiological processes that are variably modulated by bariatric surgery, influencing clinical outcomes.